Fracture strength of silicon wafers sawn by fixed diamond wire saw. (15th November 2017) - Liu, Tengyun; Ge, Peiqi; Bi, Wenbo; Wang, Peizhi
Highlights: A new model of surface crack distribution in sliced silicon wafer was developed. Theoretical results were comparable with experimental results very well. The model can predict wafer strength without considering stress state of wafers. Abstract: A larger breakage ratio occurs with the decrease of wafer thickness due to the decrease of fracture strength for as sawn silicon wafers, which is a severe problem to limit the production yield of silicon wafers. It is necessary to understand the fracture behavior of as swan silicon wafers for increasing the wafer yield. In this paper, a predictive model for wafer fracture strength is proposed according to the linear-elastic fracture mechanics. The simulation results are comparable with the experimental results from references, indicating the correctness of this proposed model. Besides that, influences of surface crack parameters on the fracture strength of silicon wafer are discussed. Results indicate that the fracture strength of silicon wafer changes less when the surface crack inclination angle between the crack plane and saw mark is between 0 and 25°. However, the fracture strength increases with the increase of the surface crack inclination angle when the angle is larger than 25°. This proposed model can predict the strength distribution of silicon wafers, and it is very helpful to understand the fracture behavior of silicon wafers.